Study of serum uric acid levels in lichen planus - Vijaya Sree, J.; Anand Kumar, V. (International Journal of Research in Dermatology, 2018)
Background: Free radicals have an important involvement in the underlying mechanism of lichen planus (LP) and also various skin diseases. The aim of the study was to evaluate serum uric acid (UA) levels as a measure of the antioxidant defense status in lichen planus patients. Methods: The duration of the present study was from September 2016 to October 2017 which includes 30 lichen planus patients and 30 other patients whose age and sex matched with the subjects served as controls. Results: Most common type of lichen planus is classical lichen planus. In our study, serum UA levels were significantly decreased in patients with respect to controls 3.1±0.91 and 4.9±1.08 mg/dl respectively. The difference of means is 1.8 mg/dl and was found to be significant (p<0.001). Conclusions: UA may be a potential, useful biomarker of antioxidant status in LP and a rational strengthening of the antioxidant defenses should be part of an optimal treatment strategy.